A 14-Year Follow-Up of a Combined Liver-Pancreas-Kidney Transplantation: Case Report and Literature Review - Zhang, Geng; Qin, Weijun; Yuan, Jianlin; Ming, Changsheng; Yue, Shuqiang; Liu, Zhengcai; Yu, Lei; Yu, Ming; Gao, Xiaokang; Zhou, Yu; Wang, Longxin; Yang, Xiaojian; et al. (Frontiers in Medicine, 2020)
Abstract Objective To investigate the long-term effect of triple organ transplantation (liver, kidney, and pancreas) in a patient with end-stage liver disease, post chronic hepatitis B, cirrhosis, chronic renal failure, and insulin-dependent diabetes mellitus chronic pancreatic and to explore the optimal surgical procedure. Case A 43-year-old man with progressive emaciation and hypourocrinia for 2 months. Results indicated exocrine pancreatic insufficiency and insulin-dependent diabetes related to chronic pancreatitis (CP) after developing end-stage hepatic and renal failure. Simultaneous piggyback orthotopic liver and heterotopic pancreas-duodenum and renal transplantation was performed in 2005. Pancreatic exocrine secretions were drained enterically to the jejunum, and the donor kidney was placed in the left iliac fossa. Patient was prescribed with prednisone, tacrolimus, mycophenolate mofetil, Rabbit Anti-human Thymocyte Immunoglobulin, and simulect for immunosuppression. Results Satisfactory hepatic and pancreatic functional recovery was achieved within 7 days post-surgery. The kidney was not functional, and continuous renal replacement therapy was used. However, the donor kidney was removed at day 16 post-surgery due to acute rejection reaction. A new renal transplantation at the same position was performed, and satisfactory kidney function from the new graft was achieved 3 days later. In 14 years of follow-up, patient has not had any rejection reactions or other complications such as pancreatitis, thrombosis, and localized infections. The patient is insulin independent with normal liver and renal functions. FK506＋Pred was used for immunosuppression, and the tac tough level maintained 3.0–4.5 ng/ml. Lamivudine was prescribed for long-term use to inhibit HBV virus duplication. Conclusion Simultaneous piggyback orthotopic liver and heterotopic pancreas-duodenum and renal transplantation is a good therapeutic option for patients with exocrine pancreatic insufficiency and insulin-dependent diabetes combined with hepatic and renal failure.